The Myzolecaniinae (Hemiptera: Coccidae): Old World vs. New World (Bollettino di zoologia agraria e bachicoltura, 2024)
Scale insects of the subfamily Myzolecaniinae (Hemiptera: Coccidae) are of particular interest because of their biology, wide distribution and morphology. Many are agricultural pests, and are known for their symbiotic relations with ants that constantly tend, clean, protect and even transport them in exchange for nutritious honeydew. Many morphological features found in these scale insects are reduced or lost entirely, presumably as a result of this symbiotic relationship. Although members of the Myzolecaniinae share many similarities, those of the New World show unique characteristics not found in the Old World coccids.
Keywords: Scale lnsects; Myzolecaniinae; Coccidae